Teks atlas kedokteran kedaruratan$C/ Michael I. Greenberg ; alih bahasa, Huriawati Hartanto M. ; editor, Rina Astikawati. - GREENBERG, Michael I.; Huriawati Hartanto M.; Rina Astikawati (Erlangga, 2007)
...jilid : ilus. ; 28 cm (6 eks.)